Franchise Business Strategy Sharia Business Management Perspective - Noor Iffatin Nadhifah; M Khoirul Muttaqin (Journal of Economics and Social Sciences (JESS), 2025)
The competition in the business world is very fierce and the uncertainty of the market provides very little opportunity for novice businessmen to start their business. The franichise business is one of the businesses in Indonesia that is in great demand and provides business solutions without hassle and minimizes business failures. The purpose of this study is to analyze franchise business strategy from the perspective of sharia business management. This research is a literature study research (library Research), the data used in this study are primary and secondary data, the theory used in analyzing this research is POAC (planning, organizing, actuating and controlling). The result of this study is that the concept and strategy of the franchise business is a form of mutually beneficial cooperation by multiplying partners or cooperation so that it is able to expand the market reach and can exploit greater market potential. In addition, in the franchise business process , it is expected that those who take a franchise business must be able to read market opportunities and manage their business